SISTEM INFORMASI TATA KELOLA ADMINISTRASI PERPUSTAKAAN STUDI KASUS SDN 1 KAYUPUTIH MELAKA - Putu Maha Putra; Ida Bagus Agung Udaya Yudhamanyu; Luh Putu Cintya Prabandari (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2024)
The library at SD Negeri 1 Kayuputih Melaka is currently processing data using Microsoft Excel. Using Microsoft Excel in the library system is still very inefficient because it cannot search for books quickly and there are often multiple book recordings, causing officers to have to re-check the main book if they want to make an annual book inventory report. Related to this, it is necessary to create a library information system that can facilitate the processing of library data. This library information system uses a system development methodology with the waterfall method and Data Flow Diagram (DFD) diagrams to create the system flow. In general, this library information system includes processing book data, loan data, return data, fine data and sign outs. This system will be managed by the admin to input and manage library data.